Perancangan Sepatu Kuda Berbahan Dasar Polymeric Foam dan Diperkuat dengan Fiber Glass - Fider Lumbanbatu; Surya Irawan; Khairuddin Tampubolon (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2022)
This study aims to obtain the best design and material for horseshoes. The research method used is experimental and research target design. This research was conducted in Medan and most of the experiments were conducted at USU University Medan. The results of this research are: it is known that horse shoes will be better if they are made using polymeric foam and reinforced with glass fiber. Furthermore, it was found that other advantages of horseshoe material made of polymeric foam reinforced fiberglass when compared to low carbon mild steel A 36 material, namely: a) Light weight, so it does not burden the horse's feet. b) Flexible, so it can adjust to the horse's hooves. c) Soft, so it can reduce the risk of injury. Horseshoe made of iron, when the horse is moving, if it hits a hard surface, it can cause a reaction force that over time can damage the horse's hooves, the joints of the horse's legs and even the horse's feet, if used for a long time. d) Resistant to chemicals found in the horse's environment, for example horse urine contained in horse stables, where horse urine contains ammonia, and is mixed with other harmful substances. e) Not slippery, thus preventing the horse from slipping and reducing the risk of injury.